DNA-based taxonomy and potential suppression of long-established names: the case of Telegonus fulgerator (Lepidoptera: Hesperiidae). Issue 4 (18th May 2020) - Pfeiler, Edward; Nazario-Yepiz, Nestor O.
Abstract : DNA data consisting of a short segment of the mitochondrial cytochrome c oxidase subunit 1 gene (COI, or cox1 ), the standard barcode segment, have previously provided evidence that the butterfly taxon Telegonus fulgerator (Hesperiidae: Eudaminae) is actually comprised of a complex of at least 10 cryptic species presently referred to as the 'fulgerator complex'. Because the 10 putative species, each with a type specimen and type locality, were diagnosed solely on the basis of nucleotide characters of the COI barcode, and because a barcode is not available from the type of the nominal taxon, the naming of the 10 species has rendered T. fulgerator a nomen dubium . Here we provide an historical background on the nomenclature of T. fulgerator, and propose a neotype in order to stabilize a name that has been in use for almost 250  years. We also summarize the few data available on geographic distributions and probable dispersal scenarios of several of the cryptic species of the fulgerator complex based on publicly available barcodes.